Know Thy Enemy : Evolving Attitudes towards "Others" in Modern Shiʿi Thought and Practice - Litvak, Meir, (Social, Economic and Political Studies of the Middle East and Asia ;, 2021)
"In Know Thy Enemy, Meir Litvak analyzes the re-articulations of the "Others" in modern Shiʻism, as a novel way to examine the formulation of modern Shiʻi identity and place in the world. Among these others, which have transformed into "enemies" in the modern period are the West, apostates, Wahhabism, Jews, Baha'is and feminism. Looking at the rhetorical themes that Shiʻi writers use, the book demonstrates the contrast between the collective positive "We" and the negative threatening "Other" as a major principle in the evolution of Shiʻism as the minority branch of Islam. It offers a complex view of Shiʻi identity combining a sense of victimhood and insecurity together with conviction of intellectual and moral superiority and long-term triumph"--